2014
DOI: 10.3109/13685538.2014.949660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequent WBC treatments on the back pain therapy in elderly men

Abstract: Cryotherapy is the application of a stimulus of a cryotherapeutic temperature below -100 °C in a period of 1-3 min in order to stimulate and use physiological reactions of human body to cold. It can be applied to specific body parts or to a whole body. Whole-body cryotherapy is a treatment method applied in treatment of motor organ issues, nervous system diseases, psychiatry, dermatology and laryngology. The research group consisted of 80 male in the age range of 65-77 suffering from chronic, lasting more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Pain levels also decreased with improvements in daily activities. A second longer study by Giemza et al (2015) involved two groups: one with daily WBC exposures, whilst the second one consisted of exposures twice a week. Exposure in the main chamber lasted for three minutes.…”
Section: Wbc Effectiveness In Internal Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Pain levels also decreased with improvements in daily activities. A second longer study by Giemza et al (2015) involved two groups: one with daily WBC exposures, whilst the second one consisted of exposures twice a week. Exposure in the main chamber lasted for three minutes.…”
Section: Wbc Effectiveness In Internal Medicinementioning
confidence: 99%
“…In the research of. Authors suggest that WBC is safe and effective in treating low back pain (Giemza et al, 2015).…”
Section: Wbc Effectiveness In Internal Medicinementioning
confidence: 99%
“…After an 8-day period, they demonstrated that the −110 • C WBC group manifested a significant improvement in spine mobility and chest expandability. Giemza et al (2015) evaluated the effects of frequent WBC (3 min, −120 • ) treatments on back pain therapy in elderly men, focusing their attention on the lumbo-thoracic spine mobility, measuring active flexion and extension, rotation to the right and the left, and lateral flexion to the right and the left. The patients who exercised and underwent WBC five times a week showed a significant increase in the range of the lumbar spine mobility.…”
Section: Flexibilitymentioning
confidence: 99%
“…A variety of studies (Ma et al, 2013 ; Giemza et al, 2015 ; Romanowski and Straburzynska-Lupa, 2020 ) have found favorable outcomes in the improvement of range of motion (ROM) and flexibility after one or multiple cryo-exposures. Ma et al ( 2013 ) studied the effects of a cycle of 24 WBC sessions (3 min, −110°C) on the active ROM of flexion, abduction, internal, and external rotation of the shoulder in subjects suffering from adhesive capsulitis of the shoulder.…”
Section: General Physiological Reactions After Wbc/pbcmentioning
confidence: 99%
“…The effectiveness of cryogenic temperature treatments is proven in the treatment and rehabilitation of several diseases like multiple sclerosis, arthrosis, chronic back pain, or fibromyalgia (14)(15)(16)(17). We also know that WBC is widely used in sports medicine (18) and may have a potentially positive effect on affective disorders (19)(20)(21), deterioration of cognitive functions (22), and worsen sleep quality (23,24) as well.…”
Section: Introductionmentioning
confidence: 99%